The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.17763/haer.78.3.8w010nq4u83348q5
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the Placement of American Indian and Alaska Native Students in Special Education Programs and Services in the Early Grades: School Readiness as a Predictive Variable

Abstract: In this article, Jacob Hibel, Susan Faircloth, and George Farkas investigate the persistent finding that American Indian and Alaska Native (AI/AN) students are overrepresented in special education. Using data from the kindergarten cohort of the Early Childhood Longitudinal Study, the authors compare the third-grade special education placement rate of AI/AN students to that of other racial/ethnic groups. They find that approximately 15 percent of AI/AN third-graders received special education services, a rate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…Unlike the Asian American population, Native American students are overrepresented in special education nationally (Dauphinais & King, 1992;Hibel, Faircloth, & Farkas, 2008;Marks, Lemley, & Wood, 2010). This group also suffers from environmental deprivation (Vraniak, 1994), high rates of suicide (CDC, 2007), and high rates of school dropout (Sparks, 2000).…”
Section: Structural Bias Research Among Asian American and Native Amementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the Asian American population, Native American students are overrepresented in special education nationally (Dauphinais & King, 1992;Hibel, Faircloth, & Farkas, 2008;Marks, Lemley, & Wood, 2010). This group also suffers from environmental deprivation (Vraniak, 1994), high rates of suicide (CDC, 2007), and high rates of school dropout (Sparks, 2000).…”
Section: Structural Bias Research Among Asian American and Native Amementioning
confidence: 99%
“…Thus far, such efforts to understand the respective roles that social, cultural, and linguistic factors have on the normative development of Native American children have identified English language skills (Beiser & Gotowiec, 2000;Dauphinais & King, 1992;Tsethlikai, 2011), cultural practices (Dauphinais & King, 1992;Tsethlikai, 2011), and school readiness (Hibel et al, 2008) as factors contributing to the educational experiences of Native American children.…”
Section: Future Researchmentioning
confidence: 99%
“…However, (Hibel, Faircloth, and Farkas (2008) found that, after controlling for socioeconomic status and characteristics of the school, there were no significant differences in the special education placement rates of American Indian and Alaska Native students with that of non-Hispanic White students. The strongest predictor in this study that used a large US database was students' reading and numeracy skills on entry to school.…”
Section: Overrepresentationmentioning
confidence: 85%
“…Although AI/AN students were not oversampled in these data sets, they are included in sufficient numbers to allow for statistical analysis. For example, using data from the ECLS-K (1998-1999), Hibel, Faircloth, and Farkas (2008) found that AI/AN students' referral and placement into special education could be predicted in kindergarten, based in large part on these children' s scores on standardized achievement tests in reading and math. This analysis indicated that those students who performed poorly on the selected achievement tests were more likely to receive special education services in the early grades.…”
Section: Large-scale National Education Data Setsmentioning
confidence: 99%